Literatura infantil: a prática pedagógica de uma professora de creche - Pessanha, Simone Eliane dos Santos (2020)
The object of this research is the pedagogical practice of a nursery teacher regarding children's literature. The questions that guided the study were: How is children's literature worked by a three-year-old teacher? How are text and image considered in the teacher's practice? The general objective was to analyze the pedagogical practice related to the Literature of a teacher who works with three year old children in a Child Education Center (CEI) located in the city of São Paulo, which we call “Estelinha”. As specific objectives, we list the following: to verify how children's literature is worked by a teacher of 3 year old children; verify how the text and the image are considered in the teacher's practice. We start from the premise that it is possible to work with children's literature with very young children and, because they are powerful, they are able to question and position themselves in front of the narratives. The research subject was a teacher who teaches for three year old children in the mentioned CEI. The methodology used was of a qualitative nature and the data collection instruments were: observation of teaching practice with an emphasis on literature, interview with the teacher and subsequent dialogue with the teacher. Data analysis was performed according to content analysis according to Bardin. Regarding the theoretical framework, we will use the following authors: Abramovich, Baptista, Coelho, Fonseca, Parreiras, Silva, Zilberman, among others. The analysis of the data allowed us to list, in addition to the main category, Children's Literature, two others, namely: a) conception of children as passive subjects in the knowledge process; b) instrumentalized pedagogical practice with regard to literature. With regard to the first category, we observed that the teacher did the reading using modalities in her voice, used onomatopoeia, told the stories in an engaging way providing the interaction of the children, pointing out the playful character of Literature. As for the second category, we noticed that the narratives with texts and images aroused the interest of the little ones and various feelings in the children, making it possible, at times, for them to participate actively, making various comments, however, at the times we were at the CEI, the choice of books always came from the teacher and children were not always able to express themselves about the stories. As for the third, category, we identified that the teacher uses criteria for the choice of books and that they have pedagogical objectives to be achieved, however, children's literature schedules have always occurred in the same way, in a vertical manner, sometimes with pedagogical purposes, without much appreciation of the aesthetic character. In view of these results and others presented in this dissertation, we saw it as fundamental that children's literature be discussed both in the initial and in the continuing education of teachers so that we can minimize the problems mentioned.